Pengaruh Ritual Api Homa terhadap Kesejahteraan Umat Buddha di Vihara Vajra Bumi Satya Dharma Wiriya, Dusun Lamuk, Temanggung - Saras Saras (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Homa Fire ritual is a spiritual practice that has developed in the Buddhist tradition for thousands of years and has become an important part of Buddhist religious life in Indonesia. This study analyzes the influence of the Homa Fire ritual on the spiritual, psychological, and social well-being of Buddhists at Vihara Vajra Bumi Satya Dharma Wiriya, Dusun Lamuk, Desa Kalimanggis, Kecamatan Kaloran, Kabupaten Temanggung. Using a qualitative phenomenological approach, this research explores participants’ experiences and perceptions of the ritual. Data were collected through in-depth interviews with ten regular participants and participatory observation during ritual practices, and analyzed using thematic analysis. The findings show that the Homa Fire ritual significantly affects three dimensions of well-being. Spiritually, participants experience greater inner peace, stronger connection to Buddhist teachings, and deeper understanding of Dharma. Psychologically, the ritual helps reduce stress, improve emotional regulation, and foster a more positive mental attitude. Socially, it strengthens community bonds, togetherness, and solidarity. Overall, the Homa Fire ritual functions as a holistic spiritual practice contributing to psychospiritual and social well-being in contemporary Indonesian society.